Spelling Achievement and Learning Behaviors of Grade 3 Students through Learning Management Using the Quizizz Game - พืชนะผล นางสาวอมรรัตน์; ทอมุด นิภาภรณ์; พันธุ์สีดา เฉลียว (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: 1) investigate the advancement in Thai spelling proficiency among third-grade children who underwent spelling development using Quizizz games, and 2) analyze the learning behaviors associated with Thai spelling of the same students who participated in spelling development via Quizizz games. The population comprised 35 third-grade students from Wat Thamma Chedi Sri Phiphat School. The research tools comprised lesson plans utilizing Quizizz games, an accomplishment assessment, and a learning behavior observation form. The statistical techniques employed for data analysis were percentage, mean, and relative gain score. The research findings were as follows: 1) Students who engaged in spelling development using Quizizz games demonstrated significant improvement in Thai spelling proficiency, achieving a mean score of 3.29 and a relative gain score of 26.93, reflecting a moderate level of advancement, 2) The students demonstrated spelling proficiency in Thai terms via Quizizz learning exercises, receiving an overall rating of "good." The intention to perform tasks exhibited the highest average score among the behaviors, succeeded by the responsibility for the tasks. Conversely, determination in task completion yielded the lowest average score. All behaviors received a favorable evaluation.